LECTURE 27: SEQUENCES MINGFENG ZHAO March 16, 2015 Sequence Definition 1. A sequence {an }∞ n=1 is an ordered list of numbers o the form {a1 , a2 , a3 , · · · , }. A sequence maybe be defined with an explicit formula of the form an = f (n) for n = 1, 2, 3, · · · . A sequence also may be generated by a recurrence relation of the form an+1 = f (an ), for n = 1, 2, 3, · · · , where a1 is given. Example 1. . Let an = a1 = − (−1)n n for all n ≥ 1, then n2 + 1 1 1 =− , 12 + 1 2 a2 = 2 2 = , 22 + 1 5 a3 = − 3 3 =− , 32 + 1 10 and a10 = Example 2. Let an+1 = 2an + 1 and a1 = 1, then a2 = 2a1 + 1 = 2 · 1 + 1 = 3 a3 = 2a2 + 1 = 2 · 3 + 1 = 7 a4 = 2a3 + 1 = 2 · 7 + 1 = 15 Question 1. Can you find an explicit formula of an in Example 1? In fact, since an+1 = 2an + 1, then an+1 + 1 = 2an + 1 + 1 = 2an + 2 = 2(an + 1). Let bn = an + 1, then bn+1 = 2bn and b1 = a1 + 1 = 2. So we get bn = bn bn−1 · bn−1 b2 ··· · b1 = 2n−1 · 2 = 2n . bn−2 b1 Therefore, we have an = bn − 1 = 2n − 1, 1 for all n ≥ 1. 10 10 = . 102 + 1 101 2 MINGFENG ZHAO Limit of a sequence Definition 2. If the terms of a sequence {an } approach a unique number L as n increase, that is, if an can be made arbitrarily close to L by taking n sufficiently large, then we say that the sequence {an } converges to L, denoted by lim an = L. n→∞ If the terms of the sequence do not approach a single number as n increases, the sequence has no limit, and the sequence diverges. Example 3. Consider the sequence (−1)n n2 + 1 ∞ , then n=1 1 − , 2 1 , 5 − 1 , 10 1 ,··· . 17 The terms decrease in magnitude and approach 0 with alternating signs. So the limit appears to be 0. Example 4. Consider the sequence {cos(nπ)}∞ n=1 , then cos(π) = −1, cos(3π) = −1, cos(2π) = 1, cos(4π) = 1, · · · . The terms of the sequence alternate between 1 and -1, and never approaches a single value. So the sequence diverges. Theorem 1. Suppose f (x) is a function such that f (n) = an for all positive integers n, if lim f (x) = L, then the limit x→L of the sequence {an } is also L. Example 5. Find the limit of the sequence Let f (x) = 3n3 an = 3 n +1 ∞ . n=1 3x3 , then f (n) = an for all n ≥ 1. Notice that +1 x3 lim f (x) = lim x→∞ x→∞ 3x3 3 = lim = 3. 3 x→∞ x +1 1 + x13 By Theorem 1, then lim n→∞ 3n3 = 3. n3 + 1 Theorem 2 (l’Hospital’s Rule). Let f (x) and g(x) be differential functions, then I. Assume that lim f (x) = lim g(x) = 0 and lim x→∞ x→∞ x→∞ lim x→∞ f 0 (x) = L, then g 0 (x) f (x) = L. g(x) LECTURE 27: SEQUENCES II. Assume that lim f (x) = ±∞, lim g(x) = ±∞ and lim x→∞ x→∞ x→∞ f 0 (x) = L, then g 0 (x) f (x) = L. g(x) lim x→∞ 3 n+5 n n ∞ . Example 6. Find the limit of the sequence an = n=1 x x x x+5 5 x+5 , then f (n) = an for all n ≥ 1. Notice that for the function f (x) = = 1+ , Let f (x) = 5 x x when x → ∞, then lim f (x) has the form 1∞ . So we should consider ln f (x), then x→∞ 5 g(x) := ln f (x) = ln 1 + x x ln 1 + x5 5 = x ln 1 + = . 1 x x Using l’Hospital’s Rule, we have lim g(x) x→∞ = 1 5 1+ x lim lim x→∞ = − x12 x→∞ = · − x52 5 1+ 5 x 5. So we know that lim f (x) = lim eg(x) = e5 . x→∞ x→∞ By Theorem 1, then lim n→∞ n+5 n n = e5 . o∞ n 1 . Example 7. Find the limit of the sequence an = n n n=1 1 1 Let f (x) = x x , then f (n) = an for all n ≥ 1. Notice that for the function f (x) = x x , when x → ∞, then lim f (x) x→∞ 0 has the form ∞ . So we should consider ln f (x), then 1 g(x) := ln f (x) = ln x x = ln x . x Using l’Hospital’s Rule, we have lim g(x) x→∞ = lim 1 x 1 1 = lim x→∞ x = x→∞ 0. 4 MINGFENG ZHAO So we know that lim f (x) = lim eg(x) = e0 = 1. x→∞ x→∞ By Theorem 1, then 1 lim n n = 1. n→∞ Theorem 3 (Squeeze Theorem for Sequences). Let {an }, {bn } and {cn } be sequences such that an ≤ bn ≤ cn for all integers n greater than some index N . If lim an = lim cn = L, then n→∞ n→∞ lim bn = L. n→∞ cos(n) . n2 + 1 Since −1 ≤ cos(n) ≤ 1, then Example 8. Compute lim n→∞ − cos(n) 1 1 ≤ 2 ≤ 2 . n2 + 1 n +1 n +1 Notice that lim − n→∞ n2 1 1 = 0 = lim 2 n→∞ n + 1 +1 By the squeeze theorem, Theorem 3, then lim n→∞ cos(n) = 0. n2 + 1 ∞ Theorem 4. Assume that the sequences {an }∞ n=1 and {bn }n=1 have limits A and B, respectively, then lim (an ± bn ) = A ± B, n→∞ lim an bn = AB, n→∞ lim can = cA, n→∞ lim n→∞ an A = , bn B where c is a real number provided B 6= 0. Example 9. By Example 5, Example 6 and Theorem 4, then n 3n3 n+5 lim −2 = 3 − 2 · e5 = 3 − 2et . n→∞ n3 + 1 n Department of Mathematics, The University of British Columbia, Room 121, 1984 Mathematics Road, Vancouver, B.C. Canada V6T 1Z2 E-mail address: mingfeng@math.ubc.ca